HUBUNGAN PARTISIPASI MASYARAKAT DALAM MUSYAWARAH RENCANA PEMBANGUNAN DESA (MUSRENBANGDES ) TERHADAP KEBERHASILAN PEMBANGUNAN FISIK DESA DI DESA SEMBULUNG KECAMATAN CLURING KABUPATEN BANYUWANGI - Agustin Indriya Ningsih, Yessy; Rahayu, Sri; Bahri, Subur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2021)
Abstract : The Relationship of Community Participation In Musrenbangdes Against The Success Of Physical Development of The Village In The Village of Sembulung Sub-District Cluring Banyuwangi . This event will be based on the research of developmental disabilities that do not comply with the construction in the village of Sembulung Sub-district Cluring Banyuwangi Regency. So these researchers analyzed each of the variables and indicators, community participation in Musrenbangdes (X), Direct Participation (X 1), Indirect Participation (X 2), physical development village (Y). The methods used in this research is quantitative methods. The population in this research is 80 people respondents using product moment later obtained research results X 1 against the Y of 0.550 the figure when compared to the price of a product the moment critique with N = 80 of 0.220 exceeds the price of criticism it means Ha Ho accepted and rejected, x 2 against Y of 0.630 the figure when compared to the price of a product the moment critique with N = 80 of 0.220 exceeds the price of criticism it means Ha Ho accepted and rejected, and X against Y of 0.318 the figure when compared to the price of a product the moment critique with N = 80 of 0.220 exceed price critique means Ha Ho accepted and rejected.